A barley SKP1‐like protein controls abundance of the susceptibility factor RACB and influences the interaction of barley with the barley powdery mildew fungus - Reiner, Tina (Mol Plant Pathol, 2015)
In an increasing number of plant–microbe interactions, it has become evident that the abundance of immunity‐related proteins is controlled by the ubiquitin–26S proteasome system. In the interaction of barley with the biotrophic barley powdery mildew fungus Blumeria graminis f.sp. hordei (Bgh), the RAC/ROP [RAT SARCOMA‐related C3 botulinum toxin substrate/RAT SARCOMA HOMOLOGUE (RHO) of plants] guanosine triphosphatase (GTPase) HvRACB supports the fungus in a compatible interaction. By contrast, barley HvRBK1, a ROP‐binding receptor‐like cytoplasmic kinase that interacts with and can be activated by constitutively activated HvRACB, limits fungal infection success. We have identified a barley type II S‐phase kinase 1‐associated (SKP1)‐like protein (HvSKP1‐like) as a molecular interactor of HvRBK1. SKP1 proteins are subunits of the SKP1‐cullin 1‐F‐box (SCF)–E3 ubiquitin ligase complex that acts in the specific recognition and ubiquitination of protein substrates for subsequent proteasomal degradation. Transient induced gene silencing of either HvSKP1‐like or HvRBK1 increased protein abundance of constitutively activated HvRACB in barley epidermal cells, whereas abundance of dominant negative RACB only weakly increased. In addition, silencing of HvSKP1‐like enhanced the susceptibility of barley to haustorium establishment by Bgh. In summary, our results suggest that HvSKP1‐like, together with HvRBK1, controls the abundance of HvRACB and, at the same time, modulates the outcome of the barley–Bgh interaction. A possible feedback mechanism from RAC/ROP‐activated HvRBK1 on the susceptibility factor HvRACB is discussed.